The Interaction Effects of Top Management Team Attributes and Environment on Organizational Growth - D. Agus Harjito; Zunaidah Sulong (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2005)
This paper attempts to explore how TMT (Top Management Team) attributes interact with environment dimensions to influence organizational growth. Specifically, this study will examine environmental dimensions as a potentially important moderator of the association between TMT attributes and organizational growth. However, the overall findings provide mixed results for the hypotheses tested. The results of direct effect show that: (1) organizational growth exhibits a significant positive relationship with TMT tenure; (2) TMT functional heterogeneity is insignificant with no change in the variance of organizational growth; and (3) positive but insignificant relationship between industrial heterogeneity and organizational growth. Furthermore, the interaction effect results indicate that: (1) as munificence increases, the relationship between TMT tenure and organizational growth shows increasingly positive; (2) concentration, dynamism and munificence moderate the relationship between TMT functional heterogeneity and organizational growth; (3) finally, the interaction effect also provide mixed results, such: as environment concentration increases, the relationship between TMT industrial heterogeneity and organizational growth increases positively; by contrast, as environment dynamism increases, the relationship between TMT industrial heterogeneity and organizational growth increases negatively; while the interaction between TMT industrial heterogeneity and environment munificence is not significant to explain the organizational growth.Key words: Organization growth, environment, management team.